O roli podręcznika w nauczaniu w szkole średniej - Ingarden, Roman; Spychalska, Natalia (Colloquia Litteraria, 2020)
This article was written on the basis of lectures delivered by the council of middle school directors in Lviv 4 IV 1938. The main idea of the article is live- -teaching and important role of a course book in didactic methods. Ingarden wrote about advantages related to the methods of interactive learning. It was first conception which he put on didactic process; and the second one was learning with a course book. The important idea of this thought was that the relation with a course book carries essential element in learning process. A course book must be organized holistically with respect to knowledge. Teacher in Ingarden framework must have a real contact with a student in a lesson, and a student must have a chance to revise the material at homehis intimate atmosphere. It gives him independence and opportunity to adapt it relatively to his own receptive skills. In the works of Aesthetic and didactis. How to combine learning about beauty with teaching Polish?, this conception is connected with the Ingarden’s idea of esthetics .